Antecedents of continuance intentions towards e – shopping among young shoppers in Kelantan - Fatin Zakirah Amanzuria (2019)
Todays, online shopping have become a great progression among young shoppers. This research paper aimed to examine the significant factors that influenced continuance intentions towards online shopping among young shoppers in Kelantan. This research was conducted by using the method of quantitative research by distributing the survey questionnaires through online that administer by Google Form. The questionnaires were spread by Whatsapps applications and besides that manual distributed also have been used. A total number of 150 respondents were collected through Kelantan using convenience sampling technique. Statistical Packages for the Social Sciences (SPSS) was used to evaluate the data that have been collected and discussed in order to figure out factors of convenience, website design/features, time saving and security influencing continuance intentions towards online shopping among young shoppers in Kelantan. Last but not least, there are several recommendations will be suggested for the future of research.